2015
DOI: 10.1155/2015/519897
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy for Localized Ureter Transitional Cell Carcinoma: Three Case Reports

Abstract: The gold standard management for ureter transitional cell carcinoma (UTCC) is radical nephroureterectomy with excision of the bladder cuff. However, some patients cannot undergo this procedure for several reasons. In the case reports described herein, we performed stereotactic body radiotherapy (SBRT) on three patients with inoperable or surgery-rejected localized UTCC. Two out of the three patients did not develop local recurrence or distant metastasis during the observation period. However, recurrence was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…Regarding safety, two individual studies published in the last few years were case reports of the use of stereotactic body radiotherapy (SBRT) for the treatment of UTUC. Maehata and Evans both reported their experience using SBRT in elderly patients with medically inoperable UTUC, and no acute or late adverse events were observed in any of the three cases (16,17). In the present study, our cases supported the clinical experience of Maehata and Evans.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding safety, two individual studies published in the last few years were case reports of the use of stereotactic body radiotherapy (SBRT) for the treatment of UTUC. Maehata and Evans both reported their experience using SBRT in elderly patients with medically inoperable UTUC, and no acute or late adverse events were observed in any of the three cases (16,17). In the present study, our cases supported the clinical experience of Maehata and Evans.…”
Section: Discussionsupporting
confidence: 86%
“…Maehata et al reported on their experience with aggressive hypofractionated radiation therapy, using between 50 and 60 Gy in 10 fractions in 3 elderly patients with medically inoperable UUTUC. 26 In all 3 cases, this hypofractionated regimen was effective at controlling the treated tumor. One patient, who had a primary lesion in the distal ureter, experienced an out-of-field bladder recurrence 22 months after treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Maehata et al reported 3 cases of inoperable localized T2N0M0 ureter carcinoma treated with stereotactic body radiotherapy (SBRT). In their study, no acute adverse events were observed, and tumor control was obtained in 2 of the 3 patients (15). When high-dose local irradiation is delivered to T1-2 tumors, local tumor control can be achieved.…”
Section: Discussionmentioning
confidence: 93%
“…Primary tumor sites included the renal pelvis (n=3) and ureter (n=2). In reference to previous reports for RT for cancer of the upper urinary tract, clinical staging but not pathological staging was used in the present study (15,16). Two patients with stage IV (case 3 and case 5) received systemic chemotherapy and the response to the chemotherapy was so good that these patients were sent to our hospital to obtain a control of the localized residual tumors.…”
Section: Methodsmentioning
confidence: 99%